Estimating the healthcare costs of children born to pregnant smokers in England: cohort study using primary and secondary healthcare data - Vaz, Luis R.; Jones, Matthew; Coleman, Tim; Szatkowski, Lisa; Tata, Laila J.; Petrou, Stavros (Wiley, 2018)
Background and aims: Little is known about the long term economic consequences of smoking during pregnancy. We estimated the association between smoking in pregnancy and the costs of delivering healthcare to infants and children in England, and investigated which aspects of care are the key drivers of these costs.